An Overview of Experiments and Numerical Simulations on Airflow and Aerosols Deposition in Human Airways and the Role of Bioaerosol Motion in COVID-19 Transmission - Justus Kavita Mutuku; Wen-Che Hou; Wei-Hsin Chen (Aerosol and Air Quality Research)
Abstract Determining the hotspots and deposition efficiencies (DEs) for aerosols in human airways is important for both research and medical purposes. The complexity of the human airways and the breathing process limit the application of in vitro measurements to only two consecutive branches of the human airway. Herein, in-depth information on in vitro experiments and state-of-the-art review on various computational fluid dynamics (CFD) applications and finite element methods on airflow and aerosol motion in both healthy and obstructed human airways are provided. A brief introduction of the application of one-dimensional and two-dimensional mathematical models to investigate airflow and particle motion in the lungs are further discussed. As evident in this review, aerosol deposition in the upper and central human airway regions has been extensively studied under different inhalation statuses and conditions such as humidity as well as different aerosol sizes, shapes, and properties. However, there is little literature on the lower sections of the human airways. Herein, a detailed review of the fundamentals for both in vitro experiments and numerical simulation at different sections of human airways is done. Exceptional features and essential developments in numerical methods for aerosol motion in healthy and diseased human airways are also discussed. Challenges and limitations associated with the applications of in vitro experiments and CFD methods on both human-specific and idealized models are highlighted. The possibility of airborne transmission pathways for COVID-19 has been discussed. Overall, this review provides the most useful approach for carrying out two-phase flow investigations at different sections of the human lungs and under different inhalation statuses. Additionally, new research gaps that have developed recently on the role of bioaerosols motion in COVID-19 transmission, as well as the deposition of aerosols in impaired human airways due to coronavirus (COVID-19) are underlined.